The Pengaruh Competitive Psychological Climate Terhadap Career Success Melalui Work Engagement Sebagai Variabel Mediasi Pada Dosen Universitas Negeri Surabaya - Bellinda Novastra; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2025)
Competition among universities drives efforts to improve institutional quality and reputation, both of which depend on the delivery of high-quality academic services. The learning process is a core activity in higher education and represents one of the main academic services. As the primary providers of these services, lecturers play a crucial role in the teaching and learning process. These institutional demands can create competitive pressure that shapes a competitive psychological climate in the workplace. This climate can influence lecturers' career success, either positively or negatively. This study aims to analyze the effect of competitive psychological climate on career success through work engagement as a mediating variable among lecturers at Universitas. A quantitative approach was employed, using descriptive analysis through categorization and inferential analysis through Structural Equation Modelling - Partial Least Squares (SEM-PLS), supported by SmartPLS 4 software. The findings indicate that competitive psychological climate has a significant positive effect on both career success and work engagement. Additionally, work engagement has a substantial and positive impact on career success, and it has been proven to mediate the relationship between competitive psychological climate and career success. These findings highlight the importance of lecturer engagement in managing competitive environments to foster positive career outcomes at Universitas.